A Systematic Review on Sesamum indicum L.: Bridging Traditional Information and Pharmacological Indications for Future Translational Research - Shivam; Sachan, Neetu; Chandra, Phool (Current Traditional Medicine, 2023)
Background: Sesame (Sesamum indicum L., family: Pedaleaceae) is also known as Til, sesamum, beniseed, and sim-sim. Sesame is an herbaceous, tropical, erect, annually grown, and oldest oilseed plant. Sesame crop has been mainly cultivated in Asia, Africa, and different parts of the world for centuries. Objective: The aim of this systematic review on Sesamum indicum L is to bridge traditional information and pharmacological indications for future translational research. Methods: The current study of Sesamum indicum (S. indicum) on its phytochemistry, pharmacological activities, and customary uses depends on a few well-known databases, for example, ACS, Web of Science, PubMed, Scopus, Science Direct, SciFinder, Google Scholar, Wiley online library, Springer, Taylor and Francis, Pubmed, and other distributed materials, for example, course books and papers. The literature was looked at using the catchphrases ‘Sesamum indicum’ Sesamin, Sesamol, and Sesamolin, etc. Results: Based on data found during reviews, sesame possesses numerous traditional uses and activities. It also showed that different parts of the plant contain different phytoconstituents. Conclusion: Conclusively, it is found that S. indicum has been confirmed as an essential therapeutic origin from its conventional use.
Keywords: til